2018
DOI: 10.1039/c8ra03832e
|View full text |Cite
|
Sign up to set email alerts
|

Design of melt-recyclable poly(ε-caprolactone)-based supramolecular shape-memory nanocomposites

Abstract: Novel melt-recyclable poly(ε-caprolactone)/cellulose nanocrystals supramolecular nanocomposite networks with shape-memory behavior have been successfully constructed by playing with UPy chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Recently, it was shown that by incorporating cellulose nanocrystals into a melt-recyclable PCL-based polymer, the extent of the crosslinking in the networks could be adjusted, and thus the SMP properties. 33 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that by incorporating cellulose nanocrystals into a melt-recyclable PCL-based polymer, the extent of the crosslinking in the networks could be adjusted, and thus the SMP properties. 33 …”
Section: Introductionmentioning
confidence: 99%